Using Landsat data to determine urban growth in major Southeast Asian cities - Kee, Che Sheng (2017)
Asian countries have been experiencing rapid urbanisation since the past four decades. The increasing urban population is the main driving force of urbanisation. People have chosen to live in urban centres for better living conditions and because of the modern infrastructure. This accelerates the rate of urbanisation with the size of the city expanded to accommodate such increase of population. However, urbanisation brings numerous negative impacts to the environment such as depletion of natural resources, loss of biodiversity and climate change. As such, urbanisation needs to be monitored carefully and managed in sustainable ways to minimize the effect to environment. SEA region is the study area while Kuala Lumpur, Ho Chi Minh, Semarang and Da Nang are the study cities. Landsat provides wide range of satellite based imagery of the Earth since 1972. Hence, Landsat imageries are used to produce the urban maps for three years (1994, 2008 and 2015) with the aid of GIS software, ArcMap 10. The map is classified into five categories: urban, water body, vegetation, barren land and cloud cover. Relationships between three urbanisation factors: urban area, population density and road density are examined through box-whisker graphs. Ho Chi Minh is found to be the city which have the largest land to urban conversion from 1994 to 2015 amongst the four study cities. The relationship between road density and urban area is found to be linear whereas the relationships for urban area vs population density and road density vs population density exhibit quadratic or linear forms.